Chemistry of lignin and hemicellulose structures interacts with hydrothermal pretreatment severity and affects cellulose conversion. (2nd July 2021) - Deralia, Parveen Kumar; Jensen, Anders; Felby, Claus; Thygesen, Lisbeth Garbrecht
Abstract: Understanding of how the plant cell walls of different plant species respond to pretreatment can help improve saccharification in bioconversion processes. Here, we studied the chemical and structural modifications in lignin and hemicellulose in hydrothermally pretreated poplar and wheat straw using wet chemistry and 2D heteronuclear single quantum coherence nuclear magnetic resonance (NMR) and their effects on cellulose conversion. Increased pretreatment severity reduced the levels of β─O─4 linkages with concomitant relatively increased levels of β─5 and β─β structures in the NMR spectra. β─5 structures appeared at medium and high severities for wheat straw while only β─β structures were observed at all pretreatment severities for poplar. These structural differences accounted for the differences in cellulose conversion for these biomasses at different severities. Changes in the hemicellulose component include a complete removal of arabinosyl and 4‐O‐methyl glucuronosyl substituents at low and medium pretreatment severities while acetyl groups were found to be relatively resistant toward hydrothermal pretreatment. This illustrates the importance of these groups, rather than xylan content, in the detrimental role of xylan in cellulose saccharification and helps explain the higher poplar recalcitrance compared to wheat straw. The results point toward the need for both enzyme preparation development and pretreatment technologies to target specific plant species.